Mental Health, Competitive Anxiety, and Self-Confidence in Pencak Silat Athletes A Comprehensive Review Based on Psychological Aspects in Competition Preparation - Pratiwi, Alfina Diva (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore the relationship between mental health, competitive anxiety, and self-confidence in pencak silat athletes facing national and international competitions. This study is a combination of a systematic literature review approach and narrative descriptive analysis of a number of studies from journals and data reviewed from seven scientific articles discussing psychological factors of pencak silat, including stress, depression, emotional regulation, and self-efficacy. The results of the study indicate that pencak silat is not only a physical activity but also contains strong spiritual and mental content. Athletes with good mental health and high self-confidence show lower levels of competitive anxiety and more stable performance in matches. These findings emphasize the importance of psychological interventions in athlete training programs. This study suggests a continuous mental training approach to improve the psychological readiness of pencak silat athletes.